Pengaruh Gaya Kepemimpinan Partisipatif, Motivasi, dan Lingkungan Kerja Terhadap Kinerja Karyawan Milenial di Banyuwangi - Nurhakiki, Shella Maya; Widyantoro, Harry (Ekonomis: Journal of Economics and Business, 2024)
This research is a case study research carried out in 2022. The aim of this research is to assess whether participative leadership, motivation and work environment have a positive effect on the performance of millennial employees in Banyuwangi. Millennial employees in Banyuwangi are the younger generation of employees aged 20 to 28 years. To obtain data, this research used a questionnaire technique with a 5 point likert scale. The data analysis technique used in this research is descriptive analysis using partial least squares (PLS) warp analysis. The research results show that participative leadership, motivation and work environment have a positive effect on the performance of millennial employees in Banyuwangi.